Principal’s Risk Management Strategy in Realizing Quality Continuity in Educational Institutions Case Study at SMK Negeri 1 Kopang - Kurniawati, Sari; Fitriani, Mohammad Iwan (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Risk management is a critical element in maintaining continuity and improving the quality of education at SMKN 1 Kopang. This study aims to analyze the risk management strategies implemented by the school and their impact on educational quality. The findings reveal that SMKN 1 Kopang faces various risks, both internal, such as limited human resources and facilities, and external, including government policy changes and natural disasters. To address these risks, the school has implemented strategies such as teacher training, leveraging technology in management and learning, and fostering collaboration with stakeholders and external parties. The principal’s leadership plays a central role in risk management through direct supervision, regular discussions, and strengthening a collaborative work culture. The effective implementation of risk management has proven instrumental in maintaining education quality, as evidenced by the success of online learning during the COVID-19 pandemic. In the long term, SMKN 1 Kopang plans to enhance its risk management system through continuous training, the development of integrated risk policies, and strategic partnerships with various parties. This study concludes that effective risk management not only helps schools address challenges but also serves as an opportunity to sustainably enhance education quality standards. Key Words: Risk Management, Leadership, Education Quality